Theory of the exterior–interior relationship between the lungs and the large intestine to explore the mechanism of Eriobotrya japonica leaf water extract in the treatment of cough variant asthma. (5th December 2021) - He, Qian; Liu, Cui; Shen, Ling; Zeng, Linlin; Wang, Ting; Sun, Jingying; Zhou, Xia; Wan, Jun
Abstract: Ethnopharmacological relevance: Eriobotrya japonica (Thunb.) Lindl leaf (EJL) is used as a traditional Chinese medicine. E. japonica is a member of the Rosaceae family. EJL suppresses cough and relieves asthma and is widely used to treat lung diseases. In the present study, guided by the traditional Chinese medicine theory of the exterior–interior relationship between the lungs and the large intestine, the pathogenesis of cough variant asthma (CVA) and the treatment mechanism of EJL on CVA were explored. Aim of the study: This study aimed to explore the airway remodeling effects of EJL in CVA from the perspective of the intestinal flora and the matrix metallopeptidase 9/tissue inhibitor of metalloproteinases-1 (MMP-9/TIMP-1) pathway. Materials and methods: The oleanolic acid and ursolic acid contents in EJL were measured by high-performance liquid chromatography (HPLC) to ensure the quality of EJL. BALB/c mice were used to establish a CVA model through ovalbumin (OVA) sensitization and atomization. EJL (at 5, 10, or 20 g/kg/day) was intragastrically administered. The body weight, ratio of total bronchial wall area (WAt) to bronchial basement membrane perimeter (Pbm) (WAt/Pbm), the number of coughs, and cough latency were measured. The pathological changes of the lung tissue were analyzed by hematoxylin and eosin (HE) staining. The expression of α-smooth muscle actin (α-SMA) was measured by immunohistochemistry (IHC). The expressions of MMP-9 and TIMP-1 were detected in the lung tissue by reverse transcription quantitative polymerase chain reaction (RT-PCR) and Western blot analysis. Additionally, an Illumina Hiseq platform was used for 16S ribosomal DNA (16S rDNA) high-throughput sequencing to detect the intestinal flora in feces samples. Results: The results confirmed the positive effects of EJL on CVA. After administration of EJL, the number of coughs and the WAt/Pbm ratio decreased, the cough latency was prolonged, body weight was increased, and the general status was better than that of the CVA model mice. HE staining revealed that EJL decreased inflammatory cell infiltration and improved the histopathological structure of the lung tissue. EJL also showed significant inhibitory effects on the expression of α-SMA, MMP-9, and TIMP-1 and normalized the intestinal flora to a certain extent. Conclusions: The results demonstrated that EJL alleviated airway remodeling of CVA mice, which might be related to the inhibition of the MMP-P/TIMP-1 pathway and the regulation of intestinal flora. Graphical abstract: Image 1 Highlights: Cough variant asthma can cause intestinal flora disorders. Airway remodeling of cough variant asthma is related to the MMP-9/TIMP-1 pathway. MMP-9/TIMP-1 pathway may be related to intestinal flora based on the "lung-gut" axis. Eriobotrya japonica leaves have regulatory effect on the intestinal flora and MMP-9/TIMP-1 pathway.